MENINGKATKAN KEMAMPUAN BERNYANYI SISWA MELALUI COOPERATIVE LEARNING DI SMP NEGERI 1 TIUMANG KABUPATEN DHARMASRAYA - Olivia Martiana; Jagar Lumban Toruan; Ardipal Ardipal (FBS Universitas Negeri Padang, 2013)
Abstract The purpose of this research is to describe the learning process of singing at the Eighth 2 grade SMP Negeri 1 Tiumang, Dharmasraya Regency through cooperative learning. This qualitative research uses descriptive methods analysis. Techiques of data collection were observation, interview and documentation. Data were analyzed by measuring the levels of proficiency and accuracy in reading rhythm, melody and song presentation. The research was conducted by forming groups of 5 or 6 students. Each group of students consists of high, moderate and low ability in singing, and work together in their respective groups. The results showed an increase in students' ability to sing in reading rhythm, melody and song presentation after the implementation of cooperative learning.